2010
DOI: 10.1088/1674-1056/19/11/110508
|View full text |Cite
|
Sign up to set email alerts
|

Optical patterns in spatially coupled phase-conjugate systems

Abstract: Various pattern evolutions are presented in one-and two-dimensional spatially coupled phase-conjugate systems (SCPCSs). As the system parameters change, different patterns are obtained from the period-doubling of kink-antikinks in space to the spatiotemporal chaos in a one-dimensional SCPCS. The homogeneous symmetric states induce symmetry breaking from the four corners and the boundaries, finally leading to spatiotemporal chaos with the increase of the iteration time in a two-dimensional SCPCS. Numerical simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The QCT method adopted in this paper is similar to that described in the previous literatures. [23][24][25][26][27][28] In our QCT calculations, the classical Hamilton equations are integrated numerically in three dimensions. Meanwhile, for each trajectory, the numerical integration accuracy is verified by checking the conservations of the total energy and the total angular momentum.…”
Section: Theory and Computational Methodology 21 Pes And Qct Calculat...mentioning
confidence: 99%
See 1 more Smart Citation
“…The QCT method adopted in this paper is similar to that described in the previous literatures. [23][24][25][26][27][28] In our QCT calculations, the classical Hamilton equations are integrated numerically in three dimensions. Meanwhile, for each trajectory, the numerical integration accuracy is verified by checking the conservations of the total energy and the total angular momentum.…”
Section: Theory and Computational Methodology 21 Pes And Qct Calculat...mentioning
confidence: 99%
“…The CM angular distributions and the scalar properties calculated in this work are partly displayed in the following; more details can be found in Refs. [23]- [25] and [30]- [43]. The probability P r and the cross section σ of the title reaction are defined as…”
Section: Product Rotational Polarizations and Rate Constantmentioning
confidence: 99%
“…Joint compensation of dispersion and nonlinearity has been proposed within 084203-3 the regime of optical orthogonal frequency division multiplexing. [13] For the PM systems, it has also been demonstrated that the nonlinear impairments as well as the dispersion can be efficiently compensated for simultaneously by OPC-based nonlinearity compensation techniques, [14,15] and mid-nonlinearity temporal inversion (MNTI) offers the best performance almost independently of the system characteristics. [8] Another advantage of OPC-based compensation methods lies in their good performance in real time and their transparency to the modulation format.…”
mentioning
confidence: 99%